Gerakan Pelatihan Pencegahan Stunting di Desa Tasik Serai Barat - Hutabarat, Sakti; Marpaung, Noveri Lysbetti; Amri, Rahyul; Siahaan, Chandro Nainggolan; Gultom, Marlina Octa Venita; Sihombing, Taruli Devi; Hutabalian, Raja Hizkia; Pasaribu, Dewi Fitri Novita; Lutfia, Anisa; Siregar, Albert Timbul; Rajagukguk, Jelita Mianarta; Ningsi, Rani Fitri Arya; Nursaldila, Nursaldila (Journal of Community Engagement Research for Sustainability, 2023)
Stunting is a public health problem that must be taken seriously. Toddlers who experience stunting have a lower level of intelligence, making children more susceptible to disease and in the future may be at risk of decreasing productivity levels. At the end, stunting broadly can inhibit economic growth, increase poverty and widen inequality. Sustainable education is considered to be one way to reduce stunting rates. This service has the aim of increasing public knowledge including adolescents, pregnant women, and Posyandu cadres. Therefore, all of them can recognize stunting, have knowledge to prevent and manage stunting. The material of training is given to 20 participants in 60 minutes. The knowledge level of participants is measured before and after this activity through Pretest and Posttest. The results of the pretest shows that 4 participants have good knowledge, 12 participants had moderate knowledge, and 4 participants had poor knowledge. The level of knowledge increased after the presentation of the material, also through the question and answer session, namely 15 participants had good knowledge, and 5 participants had moderate knowledge. This activity succeeded in increasing public knowledge.